Formulation and evaluation of glipizide-loaded fast-dissolving tablets using husk of Plantago ovata as a superdisintegrant - Jha, Antesh Kumar; Chetia, Dipak (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of the present study was to develop fast-dissolving tablets (FDTs) of glipizide, a sulfonylurea antidiabetic drug. The husk of Plantago ovata and pregelatinized husk of P. ovata were used as disintegrating agents. Microcrystalline cellulose was used as binder and starch (soluble) was used as bulk-forming agent. The powder blends were evaluated for angle of repose, compressibility index and Hausner ratio. The results of angle of repose, compressibility index (%) and Hausner ratio ranged from 24.23±0.57 to 29.34±0.78, 15.76±0.82 to 20.12±1.25 and 1.18±0.011 to 1.25±0.019, respectively. The tablet blends were converted into tablets by using direct compression method. The tablets were evaluated for disintegration test, hardness test, friability test, drug entrapment efficiency, content uniformity tests and drug release study. Formulations, which contained pregelatinized husk of P. ovata as a superdisintegrant, showed faster disintegration, higher percentage friability and lesser hardness than formulations containing husk of P. ovata as a superdisintegrant. Drug entrapment efficiency was found to be uniform among different batches of the tablets and ranged from 97.53±0.52 to 99.72±0.45.The results of content uniformity test of all the batches were found in the official range.The batches containing husk of P. ovata as a superdisintegrant released 15%–27% of glipizide per minute and those containing pregelatinized husk of P. ovata as a superdisintegrant released more than 95% of the drug within a minute.These results revealed that pregelatinized husk of P. ovata can be used as a superdisintegrant for obtaining FDTs.